Produção de leite por vacas alimentadas com aveia forrageira (Alvena bizantina, L.) e silagem de sorgo, suplementadas com farelo de algodão - M Cardoso, Roberto; F Coelho da Silva, José; P de Mello, Roberto; A Ferreira Mota, Vicente (Revista Ceres, 2025)
This study was carried out to investigate the effect of inclusion of forage oats (Avena bizantina L.) in dry season rations for dairy cattle. Ten Holstein x Zebu x Schwitz cows were used in experiments at the Intermediate School of Agricul- ture in Florestal of the Federal University of Viçosa, Minas Gerais, Brazil. Two treatments were used in a switchback design: A — sorghum silage supplemented with cottonseed meal, and B — sorghum silage supplemented with cottonseed meal and forage oats.